Addition of cranberry to proton pump inhibitor-based triple therapy for Helicobacter pylori eradication - Mohammadreza Seyyedmajidi; Anahita Ahmadi; Shahin Hajiebrahimi; Seyedali Seyedmajidi; Majid Rajabikashani; Mona Firoozabadi; Jamshid Vafaeimanesh (Wolters Kluwer Medknow Publications, 2016)
Objective: Proton pump inhibitor-based triple therapy with two antibiotics for Helicobacter pylori eradication is widely accepted, but this combination fails in a considerable number of cases. Some studies have shown that cranberry inhibits the adhesion of a wide range of microbial pathogens, including H. pylori. The aim of this study was to assess the effect of cranberry on H. pylori eradication with a standard therapy including lansoprazole, clarithromycin, and amoxicillin (LCA) in patients with peptic ulcer disease (PUD). Methods: In this study, H. pylori-positive patients with PUD were randomized into two groups: Group A: A 14-day LCA triple therapy with 30 mg lansoprazole bid, 1000 mg amoxicillin bid, and 500 mg clarithromycin bid; Group B: A 14-day 500 mg cranberry capsules bid plus LCA triple therapy. A 13C-urea breath test was performed for eradication assessment 6 weeks after the completion of the treatment. Findings: Two hundred patients (53.5% males, between 23 and 77 years, mean age ± standard deviation: 50.29 ± 17.79 years) continued treatment protocols and underwent 13C-urea breath testing. H. pylori eradication was achieved in 74% in Group A (LCA without cranberry) and 89% in Group B (LCA with cranberry) (P = 0.042). Conclusion: The addition of cranberry to LCA triple therapy for H. pylori has a higher rate of eradication than the standard regimen alone (up to 89% and significant).